The usage of motivation in the Teaching-Learning Process of English as a second language at ninth “A” grade of General Basic Education at Unidad Educativa “Combatientes de Tapi”, in the city of Riobamba, Chimborazo Province, in the academic period, March 2021 – July 2021 - Chávez Llamuca, Jessica Susana (2022)
Motivation is the energy that drives people to achieve their goals and overcome obstacles in their lives; furthermore, it is an essential factor in the success of the teaching-learning process of English as a second language. There are several motivational strategies that teachers can implement to increase student motivation in the classroom. In this research, the usage of motivation in the Teaching-Learning Process of English as a second language at ninth “A” grade of General Basic Education at Unidad Educativa “Combatientes de Tapi” was analyzed, because some students are not sufficiently motivated. This analysis aimed to identify the motivational strategies that are being used to increase student motivation, recognize the types of motivation to which students are exposed and describe the factors that affect the motivation of students in the English class. An English teacher and 29 ninth-year "A" students were taken as the population to achieve the established objectives. The type of study developed was qualitative with an exploratory level; meanwhile, the qualitative method used was ethnographic. In addition, the observation technique was used through the application of an observation sheet to collect the necessary information. Finally, the result of this study is that since the teacher does not use motivational strategies with the same frequency, students on some school days get motivated but, on other school days, they lose that motivation in learning English.